Which factors may determine the necessary and feasible type of effectiveness evidence? A mixed methods approach to develop an instrument to help coverage decision-makers. Issue 7 (28th July 2015) - de Groot, Saskia; Rijnsburger, Adriana J; Versteegh, Matthijs M; Heymans, Juanita M; Kleijnen, Sarah; Redekop, W Ken; Verstijnen, Ilse M
Abstract : Objectives: Reimbursement decisions require evidence of effectiveness and, in general, a blinded randomised controlled trial (RCT) is the preferred study design to provide it. However, there are situations where a cohort study, or even patient series, can be deemed acceptable. The aim of this study was to develop an instrument that first examines which study characteristics of a blinded RCT are necessary, and then, if particular characteristics are considered necessary, examines whether these characteristics are feasible. Design: We retrospectively studied 22 interventions from 20 reimbursement reports concerning medical specialist care made by the Dutch National Health Care Institute (ZIN) to identify any factors that influenced the necessity and feasibility of blinded RCTs, and their constituent study characteristics, that is, blinding, randomisation and a control group. A literature review was performed to identify additional factors. Additional expertise was included by interviewing eight experts in epidemiology, medicine and ethics. The resulting instrument was called the FIT instrument (Feasible Information Trajectory), and was prospectively validated using three consecutive reimbursement reports. Results: (Blinded) RCT evidence was lacking in 5 of 11 positive reimbursement decisions and 3 of 11 negative decisions. In the reimbursement reports, we found no empirical evidence supporting situations where a blinded RCT is unnecessary. The literature also revealed few arguments against the necessity of a blinded RCT. In contrast, many factors influencing the feasibility of randomisation, a control group and blinding, were found in the reimbursement reports and the literature; for example, when a patient population is too small or when an intervention is common practice, randomisation will be hindered. Conclusions: Policy regarding the necessity and feasibility of different types of evidence of effectiveness would benefit from systematic guidance. The FIT instrument has the potential to support transparent, reproducible and well-founded decisions on appropriate evidence of effectiveness in medical specialist care.